REGRESSION ANALYSES FOR SOME GROWTH CHARACTERS AND YIELD COMPONENTS UNDER DIFFERENT LEVELS OF POTASSIUM AND ZINC FERTILIZERS IN SUNFLOWER (HELIANTHUS ANNUUS L.) - A. T. Shaker (Mesopotamia Journal of Agriculture)
A field experiment was carried out at AL-Kuba region, west north (10 Km) of Mosul city in spring and summer seasons of 2009 to study the effect of potassium and zinc on production yield and components of sunflower. Two factors were selected for this study, potassium at three levels ( zero , 40 and 60 kg K . ha-1), and zinc at the levels ( dist. water as control , 10 and 20 mg Zn L-1 dist. water ). Simple regression was used to analyses the data for the studied characters. The results showed that there was a Linear relationship between potassium levels and the following parameters : head diameter (cm), 1000 seeds wt (g) and seed yield (Ton.ha-1), where as a quadratic relationship was found between potassium levels and the quality characters i.e. No. of seeds/head, oil percentage, oil yield(Ton.ha-1), protein percentage and protein yield(Ton.ha-1), it could be estimated that the levels of 60 kg potassium .ha-1 gave a highest value among the yields of seeds and oil . On the other hand , for zinc factor, the quadratic relationships were obtained with the zinc levels and head diameter, no. of seeds/head, 1000 seeds wt. , seed yield, oil percentage, oil yield, protein percentage and protein yield characteristics. Also it was found that the levels of 16.9 and 18.3 mg zinc L -1 dist.water gave a highest value among for the yields seeds and oil.